New Born Care: Our Perspective - Benjamin M Sagayaraj; Nidhi Sharma; Lal D. V. (Indian Journal of Neonatal Medicine and Research, 2014)
A low birth weight baby is a clinical and diagnostic challenge. The neonatologists are faced with numerous neonatal intensive care unit protocols. This study was designed to review the literature of past twenty five years regarding management of neonatal jaundice, sepsis, anaemia, hypoglycaemia, jaundice and hypoxic encephalopathy in a low birth weight newborn. The low birth weight newborn baby should be intubated electively if signs of respiratory distress appear. There should be an early Doppler of cerebral arteries to predict the ischaemic changes in neonatal brain. Probiotic therapy with Bifidobacterium bifidus and Streptococcus thermophillus protects against necrotizing enterocollitis and results in incresed weight gain. Newborn intravenous lines should not be flushed with normal saline ampoules containing benzyl alcohol as preservative, as this increases the fluidity of neonatal blood brain barrier and predisposes to neonatal jaundice. Erythropoietin subcutaneous injections are most rewarding in low birth weight babies with neonatal anaemia. There is also increase in weight. Kangaroo care is useful in management of neonatal hypothermia and is also an immunological boast as the baby gets colonised with favorable microorganisms of maternal skin.